Effect of a double‐structured microporous polymer support on the catalytic activity, stability and aggregation behavior of immobilized enzymes. Issue 7 (3rd March 2015) - Yang, Haijie; Wang, Lei; Chen, Shuli; Wang, Mian; Feng, Zhiwei
<x xml:space="preserve">Abstract</x> Enzyme catalytic activities could be improved by immobilization on a double‐structured microporous polymer composite, with leaching of the immobilized enzymes being reduced to as low as zero.